Pengaruh Desain Interior Diffuser Terhadap Peningkatan Performa Diffuser Augmented Wind Turbine (DAWT) - Klistafani, Yiyin; Mukhsen, Muh Iqbal (INTEK: Jurnal Penelitian, 2018)
The main objective of numerical simulation in thisstudies is to determine the effect of diffuser’s interior design onincreasing the diffuser augmented wind turbine (DAWT)performance by observing wind velocity increment. Numericalstudies were carried out using the computational Fluid Dynamics(CFD) method through a two-dimensional steady approach withAnsys Fluent 18.2 and Ansys Workbench 18.2 software. Thepresent studies spesifically investigate the shapes of diffuser,namely flat diffuser and curved diffuser. The studies demonstratethat the curved diffuser generates stronger increment of the windvelocity than flat diffuser (at centreline), which 1.842 times thefreestream velocity, while the flat diffuser is only able to increseup to 1.742 times the freestream velocity. The curved diffusershows the highest increment of the average wind velocity alongdiffuser with the greatest increment of 78.66 % and the flatdiffuser is only able to provide average wind velocity incrementup to 44.81%. The curved interor of diffuser is able to enlarge thewake area, so the effect of the suction flow entering the diffuserbecomes stronger. Therefore, curved diffuser is better to provideDAWT performance improvements.